2014
DOI: 10.1186/1129-2377-15-20
|View full text |Cite
|
Sign up to set email alerts
|

Access to care - an unmet need in headache management?

Abstract: Access to care for headache sufferers is not always simple. A survey conducted in a large number of members of lay associations point to the existence of multiple barriers to care for headache in several European countries. Patients usually discover the existence of specialized structures with a delay of several years after the onset of their headache. Furthermore, a relevant portion of them are not satisfied with the management of their disease, partly because of the poor efficacy of treatments and partly bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 9 publications
2
23
0
1
Order By: Relevance
“…These findings concur with a 2009/2010 survey from a remote area, including 1816 individuals, which reports a social acceptance of telehealth at 77.7% (1356/1745) and a confidence level at 65.8% (1146/1742) [ 25 ]. On the other hand, another survey conducted in 2008 with a total of 1634 individuals spread over different European countries shows that 42%-81% (964/1634) of patients with headache are unsatisfied with their health care [ 9 ]. Additionally, a similar European survey from 2013 shows that 48 % (929/1935) are unsatisfied with the headache management [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings concur with a 2009/2010 survey from a remote area, including 1816 individuals, which reports a social acceptance of telehealth at 77.7% (1356/1745) and a confidence level at 65.8% (1146/1742) [ 25 ]. On the other hand, another survey conducted in 2008 with a total of 1634 individuals spread over different European countries shows that 42%-81% (964/1634) of patients with headache are unsatisfied with their health care [ 9 ]. Additionally, a similar European survey from 2013 shows that 48 % (929/1935) are unsatisfied with the headache management [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, another survey conducted in 2008 with a total of 1634 individuals spread over different European countries shows that 42%-81% (964/1634) of patients with headache are unsatisfied with their health care [ 9 ]. Additionally, a similar European survey from 2013 shows that 48 % (929/1935) are unsatisfied with the headache management [ 9 ]. The authors concluded that access and availability to health care had previously not been given enough attention when analyzing the burden of headaches [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Access to care and patient's preferences are important elements to consider when organizing an optimal service for the patients. Access variability for headache sufferers referred to a specialist is a recognized problem (Tassorelli, Farm, et al, ). A cross‐sectional study showed that MOH patients ( n = 65) preferred information to be given personally (Munksgaard et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Проведенное в Италии исследование показало, что пациенты с ГБ обнаруживают существование специализи-рованной медицинской службы по лечению ГБ, как прави-ло, через несколько лет после дебюта заболевания [14].…”
unclassified